Perangkat Lunak Keamanan Informasi Pada Mobile Menggunakan Metode Stream Dan Generator Cipher - Asep Budiman Kusdinar; Mohamad Ridwan (IC-ITECHS, 2014)
Integration method of stream and generator cipher can used to randomizing message information. Delivery of message information through email or mobile is required a good security and safety system. So can protect message information that be acceptable by receiver carefully and precise. In this article methodologies which will be applied for randomize message information is processing encryption and descryption to apply stream and generator cipher. The software of this can be used to send message information applicable to information in character secret by using key stream and generator cipher as introduction lock of message information. So with existence of this stream and generator cipher is locking authentication message information become safe and is well ensured.